2018
DOI: 10.1007/s10840-018-0370-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up in patients treated by stent implantation for post-ablation pulmonary vein stenosis

Abstract: Symptomatic PVS after AF ablation can be successfully treated by stent implantation with durable results and good clinical outcome. AF ablation is still a feasible option after stent deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A total of 7 studies reported on medical therapy after PVS angioplasty. 2 , 3 , 7 , 8 , 9 , 12 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 7 studies reported on medical therapy after PVS angioplasty. 2 , 3 , 7 , 8 , 9 , 12 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Success rates after PV angioplasty range from only 27% to 100%. 2 , 3 , 7 , 8 , 9 , 12 , 16 , 17 Neumann et al reported on a patient cohort that was treated with postinterventional DAPT. 7 , 9 Restenosis was 73% in patients undergoing PTA alone and improved significantly after the performance of PV stenting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, close monitoring seems essential, because the consequences of exercise-induced pulmonary hypertension on the pulmonary vasculature remain largely unknown. On the other hand, symptomatic stenosis often requires percutaneous (eg, balloon dilatation and stent placement) or surgical intervention, and stent implantation appears to be the treatment of choice, as a lower restenosis rate compared to balloon angioplasty 11 and good long-term outcomes 12 have been reported. Surgical intervention is considered when the percutaneous approach has failed, or irreversible pulmonary vascular remodeling has developed.…”
Section: Discussionmentioning
confidence: 99%